RHIZOMATIC EXPLORATIONS OF PRE-SERVICE EFL TEACHERS IN THE TEACHING PRACTICUM - Nizar Ibnus (IAIN Syekh Nurjati Cirebon, 2025)
Pre-service teacher professional development is dynamic rather than linear. During their participation in a real-life teaching practicum, pre-service teachers dealt with a variety of elements that formed an assemblage, including unexpected condition such as curriculum revision. Accordingly, the purpose of this phenomenological research is to investigate pre-service teachers' professional growth experiences during the teaching practicum as they adjust to the changed curriculum. The study included seventeen EFL pre-service teachers who completed a two-month teaching practicum in fourteen different schools. The teaching practicum took place in the same semester when Kurikulum Merdeka (Emancipated Curriculum) was adopted in schools. Interviews, observations, and field notes were used to obtain the data in the settings. The data were examined using thematic and situational analysis in accordance with Lian's rhizomatic system, which consists of an intellectual framework, operational space, and support structure. The findings show that the teaching practicum acted as a macrosimulation, allowing pre-service teachers to experience non-hierarchical operational history change, resulting in personal learning outcomes. Throughout the program, they were helped by technology and social networks. The teaching practicum enabled them to hone their teacher-related skills and shape their professional identity. These findings indicate the necessity for a teacher professional development program that focuses on increasing their sense of self-direction and agency.